Pancreatic cancer: Role of the immune system in cancer progression and vaccine-based immunotherapy - Amedei, Amedeo (Hum Vaccin Immunother, 2014)
Pancreatic cancer (PC) is the 5th leading cause of cancer related death in the developed world with more than 260,000 deaths annually worldwide and with a dismal 5-year survival. Surgery is the only potential hope of cure for PC, but, unfortunately, only 20% PC patients is resectable at the time of diagnosis. Therapeutic research efforts have mainly focused on improvements in radio/ chemo treatments and to date, there are only a few chemotherapeutic agents that have shown to be effective against PC, including gemcitabine with or without abraxane as well as a combination of 5-FU, leucovorin, oxaliplatin and irinotecan (the so-called FOLFIRINOX regimen). The survival of patients treated with these regimens is marginal and hence we are in urgent need of novel therapeutic approaches to treat pancreatic cancer. The success of immunotherapeutic strategies in other cancers and various evidences that pancreatic adenocarcinoma elicits antitumor immune responses, suggest that immunotherapies can be a promising alternative treatment modality for this deadly disease. PC immunotherapy treatments include passive immunotherapeutic approaches, such as the use of effector cells generated in vitro, and active immunotherapeutic strategies, which goal is to stimulate an antitumor response in vivo, by means of vaccination. In this review, we describe the immune suppressive mechanisms of pancreatic cancer and discuss recent preclinical and clinical efforts toward PC immunotherapy, including passive approaches, such as the use of antibodies and active strategies (vaccination), with a special mention of most recent treatment with CRS-207 and GVAX.